The mimosa tree - Cleaver, Vera.; Cleaver, Bill (London : Oxford University Press, 1970)
Shortly after the Proffitts arrive in the Chicago slums from North Carolina, the stepmother leaves the family and fourteen-year-old Marvella becomes the sole support for her blind father and the four younger children.
Keywords: City and town life -- Fiction; Social problems -- Fiction